PENGENALAN KONSEP GREEN ACCOUNTING KEPADA SISWA SISWI SMKN 3 CILEGON - Gita Nabila Sabila (Prodi Akuntansi, Universitas Pamulang Kampus Serang, 2025)
Environmental damage and pollution began to be felt by many people along with the development of the industrial world. Green accounting is one type of environment that describes the costs that companies have to maintain the surrounding environment. Environmental costs are costs incurred to prevent environmental pollution so that companies need to process waste generated from the company's operational activities. This community service activity is intended to realize the importance of implementing green accounting, so that we can protect the environment around us. The importance of understanding related to green accounting and the importance of implementing green accounting in reducing environmental problems, therefore the PKM team provided socialization related to the concept of green accounting and how to apply green accounting to students of SMKN 3 Cilegon regarding the concept, benefits, objectives, and how to implement green accounting. The method used is a conceptual and participatory method, namely by involving the participants in the activities carried out, both material delivery activities, fun games and discussion sessions. This community service activity will be carried out on May 2, 2024 at the Hall of SMKN 3 Cilegon and was attended by 56 students majoring in accounting at SMKN 3 Cilegon. Protecting the environment is everyone's obligation, both the community, business actors, nor the government. Hopefully this community service activity can increase and foster a sense of concern for the environment.